Schwannoma arising from hypoglossal nerve in the submandibular triangle: a case report - Kumar, S. V.; Babu, P. V. S. S. Vijaya; Prasad, K. V. Ram; Kumari, K. Lakshmi (International Journal of Research in Medical Sciences, 2017)
Hypoglossal schwannomas usually develop in the intracranial portion of the brain. The incidence of hypoglossal schwannomas of the submandibular region is extremely rare. Here we report a case of schwannoma arising from the extracranial hypoglossal nerve in the left submandibular region.